Prognostic value of “Prepectoral edema” in MR-mammography - Kaiser, Clemens G.; Krammer, Julia; Schönberg, Stefan (Anticancer research, 2017)
Background/Aim: Previous studies have indicated a highly significant correlation between invasive tumors and accompanying prepectoral edema (PE) in MR-mammography (MRM). The aim of the present study was to identify prognostic factors associated with PE as a diagnostic sign. Materials and Methods: A total of 1,109 consecutive MRM exams were included in this study. Exclusion criteria were previous operation, biopsy, intervention, chemotherapy, hormone replacement therapy (HRT) or previous mastitis. One hundred and sixty-two patients with 180 lesions were evaluated and histologically correlated. Diagnostic evaluations were performed by four experienced radiologists in consensus. Results: One hundred and eighty lesions included 104 malignant lesions (93 invasive and 11 non-invasive) and 76 benign lesions. PE was detected significantly more frequently in presence of lymphangiosis carcinomatosa ((53.8%; 14/26) vs. (9.8%; 4/41)) (p<0,000). PE significantly correlates with positive axillary nodal status ((19.4% (12/62) vs. 44.4% (12/27)) (p=0.020), as well as pathologic enhancement of the pectoral muscle (5.4% (5/93) vs. 22.7% (20/88)) (p=0,015). PE significantly correlates with higher tumor grading (G3) (33.9% vs. 13.9%) (p<0.05). There was no significant difference in a positive vs. negative estrogen (p=0.681) and progesterone (p=0.751) and/or human epidermal growth factor receptor-2 (HER-2) (p=0.726) receptor status accompanied by PE. Conclusion: The presence of PE may be a strong prognostic indicator for lymphatic spread and the cancerous infiltration of lymph nodes. It is also associated with the infiltration of the pectoral muscle, as well as high tumor grading. There is no correlation between prepectoral edema and positive tumor receptor status.